Respostas

2014-08-27T19:54:22-03:00
Olá, Maracaitu!

a) 9-x = x+9
-x-x = 9-9
-2x = 0
-2x

b) 2x - 5 = 1-6x
2x + 6x = 1 + 5
8x = 6
x = 6/8
x = 6:2/8:2
x = 3/4

c) 2(x-1) - 2x + 2 = 0
2x - 2 - 2x + 2 = 0
2x - 2x - 2 + 2 = 0
0 = 0

d) -4(x+1) + 3x + 5 = 0
-4x - 4 + 3x + 5 = 0
-4x + 3x - 4 + 5 = 0
-x + 1 = 0

e) 3(4x - 5) = 5(-x+6)
12x - 15 = -5x + 30
12x + 5x = 30 + 15
17x = 45
x = 45/17

f) 2(x-4) + 3 = 1 - 5(2-x)
2x - 8 + 3 = 1 - 10 + 5x
2x - 5x = 1 - 10 + 8 - 3
3x = 1 - 2 - 3
3x = 1 - 5
3x = -4
x = -4 / 3
2014-08-27T21:06:58-03:00
A ) 9 - x = x + 9
-x - x = 9 - 9
- 2x = 0 . ( - 1 )
2x = 0
x = 0/2
x = 0

B ) 2x - 5 = 1 - 6x
2x + 6x = 1 + 5
8x = 6
x = 6/8
x = 0,75

C ) 2 ( x - 1 ) - 2x + 2 = 0
2x - 2 - 2x + 2 = 0
2x - 2x = 2 - 2
0 = 0

D ) - 4 ( x + 1 ) + 3x + 5 = 0
- 4x - 4 + 3x + 5 = 0
- 4x + 3x = 4 - 5
- x = - 1 . ( - 1 )
x = 1

E ) 3 ( 4x - 5 ) = 5 ( - x + 6 )
12x - 15 = - 5x + 30
12x + 5x = 30 + 15
17x = 45
x = 45/17
x = 2,64

F ) 2 ( x - 4 ) + 3 = 1 - 5 ( 2 - x )
2x - 8 + 3 = 1 - 10 + 5x
2x - 5x = 1 - 10 + 8 - 3
- 3x = - 4 . ( - 1 )
3x = 4
x = 4/3
x = 1,33

Tenha bons estudos !